Implementation of The Principal's Leadership Style Based on Qs. Ali Imran Verse 159 - Endang Zenal; An-An Andari; Andi Warsino; M Nasor (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
As time progressed, scientific leadership began to develop along with the growth of scientific management, which is better known as the science of leading. Leadership is a very important thing in school-based management. Principals as leaders have different leadership styles according to their character. Leadership characteristics contained in Qs. Ali Imran verse 159, namely: Meek and gentle. Being soft-hearted makes a leader more sensitive to what is happening around him. He is able to feel what other people feel. The research method used is a qualitative approach, namely field research. as a key instrument. In this research, the method used to collect data was observation, interviews, and documentation. Writing results: (1) a leader must be able to be a unifier in the midst of the diversity of Muslims and is also expected to be able to advance the lives of Muslims in the future; (2) There are many stories in the Qur'an that describe how a leader carries out his duties as a leader, it can help success educators while carrying out their duties; (3) Quality or good qualities in educational institutions must be built as early as possible which can be grown through the family environment. Reflections of a leader's good attitude include factors, one of which arises through religious norms.